A Phase 1 Study of KHK4083: A Single‐Blind, Randomized, Placebo‐Controlled Single‐Ascending‐Dose Study in Healthy Adults and an Open‐Label Multiple‐Dose Study in Patients With Ulcerative Colitis. Issue 8 (29th January 2021) - Furihata, Kenichi; Ishiguro, Yoh; Yoshimura, Naoki; Ito, Hiroaki; Katsushima, Shinji; Kaneko, Etsuji; Shimabe, Munetake; Mukai, Mayumi; Watanabe, Risa; Morishige, Takuya
Abstract: OX40 plays an essential role in maintaining late T‐cell proliferation and survival by suppressing apoptosis and by inducing T‐cell memory formation. Here, we report the results of the phase 1 study of KHK4083, a fully human antimonoclonal antibody specific for OX40. In this study, we aimed to assess the safety and tolerability of a single intravenous or subcutaneous administration of KHK4083 compared with placebo in healthy Japanese and Caucasian subjects and determined the pharmacokinetics (PK) and immunogenicity. Also, we assessed the preliminary efficacy and pharmacodynamics of multiple intravenous doses in Japanese patients with moderate to severe ulcerative colitis (UC). Drug‐related treatment emergent adverse events occurred in 21 healthy subjects (58.3%) and 5 patients with UC (62.5%) after administration of KHK4083. There were no serious adverse events. The PK profile of a single intravenous dose of 10 mg/kg KHK4083 was similar in healthy Japanese and Caucasian subjects. Of 8 UC patients, a clinical response was observed in 3 patients (37.5%) and clinical remission in 2 patients (25.0%) in week 6. Our study demonstrated the safety and tolerability of single and multiple administrations of KHK4083 in healthy Japanese and Caucasian subjects and Japanese patients with moderate to severe UC. It also indicated favorable pharmacological properties of the drug.